PENGARUH UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP EXPECTED EARNINGS DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING - Ali Akbar (Al Birru: Jurnal Keuangan dan Perbankan Syariah, 2023)
Abstract The objective of this study is to examine the influence of company size and leverage on expected earnings with earnings management as intervening variable. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange for the period of 2012-2015. 59 companies were obtained as the sample of this study determined based on purposive sampling method, so that the numbers of observation obtained in this study were as many as 236 units of observation for four years observation period. Based on path analysis, the results showed that company size and leverage have significant influence to earnings management. The results also showed that company size, leverage and earnings management have significant influence on expected earnings. However, the relationship between company size and expected earnings is not proven to be mediated by earnings management as an intervening variable. Likewise, leverage and expected earnings relationship is also not proven to be mediated by earnings management as intervening variables. Keywords: company size, leverage, expected earnings, earnings management